Incidence of stroke in the diabetic and non-diabetic population in Upper Austria (2008-2012) and (Austrian Journal of Statistics, 2015)
Abstract: Background and Purpose: Although it is generally known that diabetes has a negative effect on the stroke incidence, only a limited number of long-term population-based studies focus on the comparison of incidence rates of stroke in diabetics and non-diabetics. Hence, the aim of this study was to estimate the risk of stroke in the diabetic and the non-diabetic population with the help of incidence rates and effect measures. Methods: For this study, data from the Upper Austrian stroke register and the statutory Upper Austrian health insurance (1.3 million members) was used to analyse all first strokes from 2008-2012. This was done by assessing stroke incidence for the total, the diabetic and the non-diabetic population. The analysis was mainly conducted on an age/sex-specific basis. Moreover, age/sex-standardized incidence rates were calculated as well. In addition, effect measures like the relative risk, the attributable risk among exposed and the population attributable risk were computed. Results: Out of the total cohort of 1,319,761 subjects, 17,663 had a first stroke (mean age (Sd.): 71.6 (±14.3) years; 46.0 per cent male). Among these, 19.5 per cent were classified as diabetics. Concerning the stroke standardized incidence rates of the Upper Austrian population (per 100,000 person years), the following results were obtained for the diabetic and the non-diabetic population respectively: men: 571.9 (95%-confidence interval: 530.1-613.6), 319.3 (95%-confidence interval: 311.3-327.2); women: 600.9 (95%-confidence interval: 559.3-642.5), 343.5 (95%-confidence interval: 335.7-351.3). The age-standardised relative risk was found to be 1.79 (95%-confidence interval: 1.66-1.93) for men and 1.75 (95%-confidence interval: 1.63-1.88) for women. Attributable risks among exposed are as follows: men: 0.44 (95%-confidence interval: 0.40-0.48); women: 0.43 (95%-confidence interval: 0.39-0.47). For the population attributable risks 0.08 (95%-confidence interval: 0.04-0.11) was obtained for men and 0.07 (95%-confidence interval: 0.04-0.09) for women. Conclusion: This investigation showed that the stroke risk in the diabetic population is significantly higher compared to the non-diabetic population.